2021
DOI: 10.1186/s12876-021-02072-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of several blood lipid-related indexes in the screening of non-alcoholic fatty liver disease in women: a cross-sectional study in the Pearl River Delta region of southern China

Abstract: Background Lipid metabolism disorders play a critical role in the progression of non-alcoholic fatty liver disease (NAFLD). However, the number of studies on the relationships among blood lipid-related indexes and NAFLD is limited, and few studies have emphasized the comparison of blood lipid-related indexes in the same population to identify the optimal index for NAFLD screening. This study aimed to investigate the relationships among several blood lipid-related indexes and NAFLD, and to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…The ROC analyses also showed that there was a significantly better ability of CMI for identifying MAFLD among female, young and nonobese subjects. Similar to our findings, a cross-sectional study in the Pearl River Delta region of southern China found that CMI was a recommended indicator for screening women for nonalcoholic fatty liver disease (NAFLD) and could be used to detect high-risk NAFLD (44). As the metabolism, body composition, and coexisting diseases changed with aging (45-47), and the higher excessive fat accumulation of young people caused by dietary irregularities and insufficient exercise, it was reasonable that the performance of CMI may be influenced by age (48).…”
Section: Discussionsupporting
confidence: 88%
“…The ROC analyses also showed that there was a significantly better ability of CMI for identifying MAFLD among female, young and nonobese subjects. Similar to our findings, a cross-sectional study in the Pearl River Delta region of southern China found that CMI was a recommended indicator for screening women for nonalcoholic fatty liver disease (NAFLD) and could be used to detect high-risk NAFLD (44). As the metabolism, body composition, and coexisting diseases changed with aging (45-47), and the higher excessive fat accumulation of young people caused by dietary irregularities and insufficient exercise, it was reasonable that the performance of CMI may be influenced by age (48).…”
Section: Discussionsupporting
confidence: 88%
“…The comprehensive computer literature search from PubMed, MEDLINE, Web of Science, EMBASE and the Cochrane Library revealed 4722 articles, as shown in Figure 1 . Ultimately, 20 studies involving 165,725 participants were included [ 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“… 9 , 14–16 Meanwhile, studies have demonstrated that the TyG index changes with the development of MAFLD. 11 , 17 , 18 However, most of these studies are cross-sectional. Therefore, we designed this cohort study to investigate the longitudinal association of baseline TyG index with the risk of incident MAFLD in the Chinese.…”
Section: Introductionmentioning
confidence: 99%